APLIKASI LATIHAN TES IQ MENGGUNAKAN ANDROID - Sopiah, Nyimas; Ependi, Usman (Universitas Bina Darma, 2014)
Prior to formal IQ test, individuals often use the media in a book or website exercise IQ test. Lately the media has been very popular with smartphone. To accommodate the facility smartphone, then the author will make an IQ test Android-based application that can be used as training media. The purpose of the study is to make an application exercise test IQ for the user to test his ability. This application is an application that used as a training tool for users to perform an IQ test. Application development method used is a wireless application development, which consists of planning, analysis of mobile users, scenario analysis, architecture design, implementation, testing, deployment, customer evaluation, and maintenance. Given the time constraints, the method of application development is used only to implementation. This application is used IQ tests using the Android operating system used in mobile phones based on Android.